Protection of Wooden Materials Modern Methods (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
During the exploitation of wooden materials they are exposed to various impacts. At present, there are various methods of protection. Various modern methods of protection have been developed that meet the design requirements. The article provides information on modern methods of protection and the results of the analysis provided.